2014
DOI: 10.17503/agrivita-2014-36-2-p112-119
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration on the Growth of Rubber Planting Materials by Using Foliar Application of Humic Acid

Abstract: The best rubber planting materials are needed to build the best rubber plantation. Humic acids could be used to improve the growth of rubber planting materials. Humic acid plays a role as a hormone-like substance. This research was aimed to determine the optimal concentration of foliar application of humic acid in order to enhance the growth of rubber tree planting materials. This research was arranged in a completely randomized block design with five treatments and four replicates. The treatments were the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Wasson et al (2012) remarked that a root system with greater FRLD in deeper soil could uptake water and nutrients at high efficiency. Cahyo et al (2014) reported that root growth and performance were more obvious than other vegetative parts under the HSA. It could serve as auxin and promote cell enlargement by stimulating the cell wall loosening leading to greater vegetative growth (Jindo et al, 2012).…”
Section: Development Of the Fine Root Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wasson et al (2012) remarked that a root system with greater FRLD in deeper soil could uptake water and nutrients at high efficiency. Cahyo et al (2014) reported that root growth and performance were more obvious than other vegetative parts under the HSA. It could serve as auxin and promote cell enlargement by stimulating the cell wall loosening leading to greater vegetative growth (Jindo et al, 2012).…”
Section: Development Of the Fine Root Traitsmentioning
confidence: 99%
“…It enhances microbial activities and a population that transform insoluble mineral nutrients into available nutrient form for plant in the soil, thus higher soil nutrient content (Li et al, 2019). In humic acid-treated soil, pH buffering capacity, organic matter, and cation exchange capacity were improved with more significant soil physical properties resulting in enhanced root performances like fine root proliferation and nutrient uptake (Buyukkeskin et al, 2015;Cahyo et al, 2014). It was reported that the growth rates of nursery and immature rubber plants were enhanced by reducing chemical fertilizer usages and supplementing a humic acid application (Dharmakeerthi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sedangkan secara langsung asam humat terlibat dalam proses metabolisme dalam tanaman seperti meningkatkan respirasi akar, sintesis protein, dan asam nukleat (Piccolo et al, 1992). Pengaruh pemberian asam humat pada pembibitan tanaman karet sudah dilaporkan oleh Cahyo et al (2014), tetapi belum diketahui pengaruh pemberian asam humat terhadap peningkatan efektivitas pemupukan anorganik tunggal. Penelitian ini bertujuan untuk mengetahui peningkatan efektivitas pemupukan anorganik tunggal dengan pemberian asam humat pada pembibitan tanaman karet dalam polibag.…”
Section: Pendahuluanunclassified
“…juga melaporkan adanya peningkatan produktivitas tanaman jagung pada pemberian asam humat tanpa pemupukan anorganik yang tidak signifikan atau dengan peningkatan hanya sebesar 3,5% dibandingkan tanpa pemupukan. Pertumbuhan tinggi tanaman, diameter batang, bobot akar, bobot tanaman, dan kandungan hara NPK daun bibit tanaman karet pada pemberian asam humat yang tidak meningkat secara signifikan juga sudah dilaporkan olehCahyo et al (2014) tetapi dengan cara penyemprotan melalui daun. Prosiding Seminar Nasional Pembangunan dan Pendidikan Vokasi Pertanian Politeknik Pembangunan Pertanian Manokwari, 23 Juli 2022 e ISSN : 2774-1982 DOI : https://doi.org/10.47687/snppvp.v3i1.344 666KESIMPULAN DAN SARANPemberian asam humat dapat meningkatkan efektivitas pemupukan tunggal dengan mengurangi dosis hingga 50% yang ditunjukkan dengan pertumbuhan tinggi tanaman, diameter batang, bobot akar (basah dan kering), dan bobot tanaman (basah dan kering) yang tidak berbeda nyata terhadap perlakuan pupuk tunggal dosis 100%.…”
unclassified
“…It is well known that rhizosphere bacteria [ 10 , 11 , 12 ], as well as humic substances [ 13 , 14 , 15 ], stimulate plant growth when used individually. Although much less is known about their effect on trees than on herbaceous plants, it has been found that both humates [ 16 , 17 ] and rhizosphere bacteria [ 18 , 19 ] enhance the growth of woody plants. However, only a few studies have addressed the simultaneous application of these biostimulants.…”
Section: Introductionmentioning
confidence: 99%